2009
DOI: 10.2174/157340109787314703
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Nutritional Quality of Protein and Lipid Recovered from Fish Processing by-Products and Underutilized Aquatic Species Using Isoelectric Solubilization / Precipitation

Abstract: The isoelectric behavior of food proteins has been well characterized in the food science literature. The isoelectric point (pI) of a protein is a pH at which the protein maintains a zero net electrostatic charge. In this state, protein-protein hydrophobic interactions overcome protein-water electrostatic interactions and the minimum solubility of proteins results. Consequently, several food science laboratories have begun active research on the application of the pI to recover functional muscle proteins, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 68 publications
0
30
1
1
Order By: Relevance
“…Therefore, technologies facilitating more efficient use of natural resources to fulfill human nutritional needs are required. The terms "offal," "waste," and "by-products" (sometimes referred to as "co-products") are used frequently and interchangeably to describe the secondary products generated as a result of muscle food (seafood, meat, and poultry) processing and may include both edible and inedible materials left over following processing of the primary product (Gehring, Davenport, & Jaczynski, 2009). Unfortunately, "offal" and "waste" often conjure up negative connotations because these terms imply that those materials have no value and need to be disposed of.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, technologies facilitating more efficient use of natural resources to fulfill human nutritional needs are required. The terms "offal," "waste," and "by-products" (sometimes referred to as "co-products") are used frequently and interchangeably to describe the secondary products generated as a result of muscle food (seafood, meat, and poultry) processing and may include both edible and inedible materials left over following processing of the primary product (Gehring, Davenport, & Jaczynski, 2009). Unfortunately, "offal" and "waste" often conjure up negative connotations because these terms imply that those materials have no value and need to be disposed of.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, "offal" and "waste" often conjure up negative connotations because these terms imply that those materials have no value and need to be disposed of. On the other hand, the terms "by-product" or "co-product" imply that there could be some value in the secondary products and, if they are recovered properly, they could be valuable (Gehring et al, 2009). Therefore, the food industry and scientific literature should refer to these materials as "by-products" or "co-products" instead of "offal" or "waste" so that the negative consumer bias towards value-added products made using these materials would be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…ACS or ALS/isoelectric precipitation efficiently recovers nutritious proteins from sources that are difficult to process using conventional technology. The high efficiency and recovery rate possible with this process may yield proteins with increased functionality and oxidative stability compared with those recovered using conventional technology (Kelleher and Hultin 2000; Gehring and others 2009). Thus, isoelectric solubilization/precipitation may provide an efficient way to better process underutilized protein resources.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline and acid solubilization processes separated protein properly from other unwanted fractions, such as lipid and other impurities (e.g. bones, scale, skin, insoluble proteins) (Gehring et al 2009), thereby concentrating the proteins in the ACDS and ALDS samples. In contrast, the acid -alkaline solubilization method recovered both the sarcoplasmic protein that was not removed completely in the washing step and the additional fraction of myofibrillar protein (Kristinsson and Liang 2006), which led to the higher protein content of the ACDS and ALDS samples.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, conventionally processed surimi-like material had the highest gel strength among all samples. Gehring et al (2009) reported that proteins recovered through isoelectric solubilization/precipitation can be used directly or as the main ingredient in human food products. The proteins recovered by such processes are called surimi or surimi-like material.…”
Section: Introductionmentioning
confidence: 99%